2021
DOI: 10.1136/bjophthalmol-2021-319072
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring guides the management of patients with chronic non-infectious uveitis treated with adalimumab: a retrospective study

Abstract: AimTo assess the relevance of therapeutic drug monitoring (TDM) of adalimumab (ADA) treatment for the control of intraocular inflammation and treatment adjustment in chronic non-infectious uveitis (CNIU).MethodsRetrospective study of CNIU patients treated with ADA and for whom at least one dosage of serum ADA level and an antibodies against ADA (AAA) serology were performed, between June 2003 and July 2019.ResultsA total of 44 ADA-treated patients benefited from a TDM. A total of 48/79 (61%) TDM were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Assuming this is the case, it would be of great importance to monitor ADAbs levels throughout treatment to differentiate between transient and permanent antibody positivity, since only the latter is associated with subtherapeutic drug levels and with a higher risk of treatment failure. Subsequent studies have confirmed the relationship between a worse clinical response with lower trough ADA levels, which in turn are frequently found in patients with ADAbs [ 17 , 61 , 70 , 92 ]. Despite most studies in NIU having shown a protective effect of immunomodulatory therapy against the development of immunogenicity [ 17 , 61 , 70 ] in accordance with previous reports in other pathologies, Cordero-Coma et al [ 18 ] did not observe such an effect.…”
Section: Therapeutic Drug Monitoring Of Anti-tnfα In Niumentioning
confidence: 85%
See 1 more Smart Citation
“…Assuming this is the case, it would be of great importance to monitor ADAbs levels throughout treatment to differentiate between transient and permanent antibody positivity, since only the latter is associated with subtherapeutic drug levels and with a higher risk of treatment failure. Subsequent studies have confirmed the relationship between a worse clinical response with lower trough ADA levels, which in turn are frequently found in patients with ADAbs [ 17 , 61 , 70 , 92 ]. Despite most studies in NIU having shown a protective effect of immunomodulatory therapy against the development of immunogenicity [ 17 , 61 , 70 ] in accordance with previous reports in other pathologies, Cordero-Coma et al [ 18 ] did not observe such an effect.…”
Section: Therapeutic Drug Monitoring Of Anti-tnfα In Niumentioning
confidence: 85%
“…Significantly higher trough ADA levels have been consistently reported in patients with NIU who responded to treatment compared to those non-responders. In addition, ADA trough levels have shown an inverse correlation with anti-ADA antibody levels [ 17 , 18 , 61 , 70 , 92 ]. Consequently, the presence of anti-ADA antibodies has been associated with treatment failure as assessed by a worse uveitis outcome and failure to achieve remission.…”
Section: Therapeutic Drug Monitoring Of Anti-tnfα In Niumentioning
confidence: 99%
“…There are no established guidelines for the role of therapeutic drug monitoring (TDM) in patients receiving TNFis for NIU, although several studies showed that it may be beneficial. Sejournet et al, in their study on TDM in patients with chronic NIU, reported an ADA frequency of 13.6% among patients treated with adalimumab. Their results also showed that ADA formation and low drug levels together with clinical evidence of therapy failure were associated with increased adalimumab dose frequency in 13 of 31 patients (42%), an increased dose in 1 of 31 patients (3.2%), and intraclass or interclass switching in 10 of 31 patients (32%), suggesting that TDM may be useful in determining the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, patients with ADA had a lower MDL, a finding that has been confirmed in other retrospective studies of NIU. 5 In a multivariate analysis, a 1 AU/mL increase in ADA level was associated with a 0.024 μg/mL decrease in drug concentration (P < .001). An adalimumab drug level greater than 3.3 μg/mL showed good sensitivity and low specificity with an area under the curve of 0.67 for the prediction of complete response.…”
mentioning
confidence: 89%
“…The mean drug level (MDL) and mean antibody level (MAL) were 9.72 μg/mL and 84.2 arbitrary units (AU)/mL, respectively. Overall, patients with ADA had a lower MDL, a finding that has been confirmed in other retrospective studies of NIU . In a multivariate analysis, a 1 AU/mL increase in ADA level was associated with a 0.024 μg/mL decrease in drug concentration ( P < .001).…”
mentioning
confidence: 95%